REGULATION ON FOREIGN INVESTMENT RESTRICTIONS AND NOMINEE PRACTICES IN INDONESIA - David Kairupan (Fakultas Hukum Universitas Gadjah Mada, 2013)
Certain provisions of Presidential Regulation No. 36 of 2010 concerning Negative Investment List are not clearly stipulated. In relation to the restrictions of foreign investment in certain business sectors asspecified in the Negative Investment List Article 33 para. (1) and (2) of the 2007 Investment Law expressly prohibits investors from entering into any nominee shareholding documentation. Notwithstanding, manynominee shareholding practices are still employed in Indonesia, aiming to circumvent such restrictions.This paper addresses certain issues on Presidential Regulation No. 36 of 2010 and nominee shareholding practices in Indonesia. Beberapa ketentuan dalam peraturan Presiden No. 36 Tahun 2010 yang mengandung ketentuan Daftar Negatif Investasi tidak dirumuskan secara jelas. Sehubungan dengan pembatasan kepemilikan modal asing di beberapa sektor usaha, Pasal 33 ayat (1) dan (2) Undang-Undang Penanaman Modal No. 25 Tahun 2007 secara tegas melarang penanam modal membuat dokumen-dokumen yang terkait dengankepemilikan saham secara nominee. Namun demikian, praktik kepemilikan saham secara nominee masih sering dilakukan di Indonesia untuk menghindari pembatasan tersebut. Tulisan ini akan membahasbeberapa permasalahan yang berhubungan dengan Peraturan Presiden No. 36 Tahun 2010 dan praktek kepemilikan saham secara nominee di Indonesia.